2015
DOI: 10.1166/jbn.2015.1910
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin Encapsulated in Long-Circulating pH-Sensitive Liposomes as a Radiotracer for Breast Tumor Identification

Abstract: Bombesin (BBN) is a tetradecapeptide that binds specifically to gastrin-releasing peptide receptors in humans. These receptors are over-expressed in several forms of cancer; radiolabeled BBN could therefore be used to detect such cancers. However, the degradation of peptides is a critical issue in the development of tumor tracers. Liposomes can be used to overcome this problem and improve the uptake of tracers by tumors. Therefore, the purpose of this study was to prepare and characterize long-circulating and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Nanoparticles are extensively phagocytosed by macrophages present in the liver and spleen organs [25,26,46,47]. As predicted, the biodistribution studies showed high uptake in liver and spleen for 99m Tc-SpHL-DTPA-PTX and 99m Tc-SpHL-folate-DTPA-PTX.…”
Section: Discussionmentioning
confidence: 79%
“…Nanoparticles are extensively phagocytosed by macrophages present in the liver and spleen organs [25,26,46,47]. As predicted, the biodistribution studies showed high uptake in liver and spleen for 99m Tc-SpHL-DTPA-PTX and 99m Tc-SpHL-folate-DTPA-PTX.…”
Section: Discussionmentioning
confidence: 79%
“…This finding might be explained by the extensive phagocytosis typically experienced by nanoparticles after intravenous injection [4042]. The substantial uptake in kidneys (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…99m Tc-PTX showed time-dependent accumulation and tumor-to-muscle ratios superior than 1.5. This fact could be explained by the long blood circulation time, leading to more passages through the tumor region, favoring 99m Tc-PTX extravasation and therefore, tumor accumulation [3742]. …”
Section: Discussionmentioning
confidence: 99%
“…Various radiolabeled ( 111 In, 64 Cu, 99M Tc, 68 Ga, 18 F) BnR-agonists(primarily for GRPR) image[118–122] or allow targeted-delivery of cytotoxic-radioisotopes( 177 Lu) to bind to breast-cancer-cells both in vitro [118,120–122] and in vivo to image breast-cancers xenografts in nude-mice[120123]. In a comparative study in vivo of xenografts of breast-cancers in nude-mice, a 68 Ga-labeled-BnR-agonist showed greater tumor-uptake than a commonly used PET-imaging agent, 18 FDG.…”
Section: Bn-peptides-bnr: Breast-cancermentioning
confidence: 99%
“…99m Tc-labeled-liposomes conjugated to a BnR-agonist demonstrate high-uptake and strong scintigraphy images of breast-cancers xenografts in nude-mice[101,123]. Heterodiameric-PET-probes combining the RGD sequence, which binds to α(v)β(3)-integrins[119] and a BnR-agonist to various radioisotopes( 18 F, 64 Cu, 68 Ga) demonstrates high-uptake and the ability to image breast-cancer-cells in xenografts in nude-mice.…”
Section: Bn-peptides-bnr: Breast-cancermentioning
confidence: 99%